2012
DOI: 10.1097/aln.0b013e318267395b
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Age as a Prognostic Marker of 1-year Poor Outcome for Subarachnoid Hemorrhage Patients through Its Interaction with Admission Hydrocephalus

Abstract: In this observational study, elderly age and admission hydrocephalus predicted poor outcome, but elderly age without hydrocephalus did not. An external validation, however, will be needed to generalize this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 51 publications
6
15
1
Order By: Relevance
“…demonstrated that prenatal morphine exposure differentially altered the performance of adult male and female rats on tasks requiring learning and spatial memory (Slamberova et al, 2001a). Another group reported disturbance in a passive avoidance retention task in females after intrauterine morphine treatment (Degos et al, 2012). We found a significant gender-treatment interaction in the case of stressorinduced blood glucose elevation as well (Fig.…”
Section: Animal Studiessupporting
confidence: 58%
“…demonstrated that prenatal morphine exposure differentially altered the performance of adult male and female rats on tasks requiring learning and spatial memory (Slamberova et al, 2001a). Another group reported disturbance in a passive avoidance retention task in females after intrauterine morphine treatment (Degos et al, 2012). We found a significant gender-treatment interaction in the case of stressorinduced blood glucose elevation as well (Fig.…”
Section: Animal Studiessupporting
confidence: 58%
“…18,23,24 The rate of poor outcome and mortality at 1 year in our cohort was lower than the results reported in other previous studies. 7,22,25 It may be because that the cut-off age for elderly patients in our study was 60 years old and younger than these previous studies. After classification of age, our results shown 75 years old is a critical age which affecting outcome for elderly aSAH patients underwent EVT.…”
Section: Discussionmentioning
confidence: 52%
“…5,6,11,25 However, the contribution made by each specific predictor remains unknown for elderly aSAH patients. Not surprisingly, Fisher grade has the most profound influence on 1-year poor outcomes, followed by periprocedural complications and Hunt–Hess grade.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even if elderly patients (70 years) present comorbidities that may hamper the clinical outcome, 37 % of them will have a good clinical outcome at long-term follow-up after endovascular coiling of a ruptured aneurysm, independently from the initial WFNS score at admission [100]. However, hydrocephalus in elderly patients may be associated with a worse clinical outcome [101]. Finally, some scores combining clinical and biomarker data, like the ABC score [102], have been proposed to predict the 1-year clinical outcome in patients with coiled ruptured aneurysms.…”
Section: Prognostic Factorsmentioning
confidence: 96%